2014
DOI: 10.1002/tox.22031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of TiO2 nanoparticle‐induced neurotoxicity in zebrafish (Danio rerio)

Abstract: Zebrafish (Danio rerio) has been used historically for evaluating the toxicity of environmental and aqueous toxicants, and there is an emerging literature reporting toxic effects of manufactured nanoparticles (NPs) in zebrafish embryos. Few researches, however, are focused on the neurotoxicity on adult zebrafish after subchronic exposure to TiO2 NPs. This study was designed to evaluate the morphological changes, alterations of neurochemical contents, and expressions of memory behavior-related genes in zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 92 publications
1
34
0
1
Order By: Relevance
“…TiO 2 nanoparticle toxicity has been extensively examined in the context of freshwater and marine environments and in organisms belonging to several trophic levels 4548 . It is generally thought that oxidative stress is the primary mechanism of acute toxicity to developing organisms due to the ability of forms of TiO 2 to produce reactive oxygen species (ROS) when irradiated 4952 . ROS leads to cell death via protein, lipid, and DNA damage 45, 46, 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 nanoparticle toxicity has been extensively examined in the context of freshwater and marine environments and in organisms belonging to several trophic levels 4548 . It is generally thought that oxidative stress is the primary mechanism of acute toxicity to developing organisms due to the ability of forms of TiO 2 to produce reactive oxygen species (ROS) when irradiated 4952 . ROS leads to cell death via protein, lipid, and DNA damage 45, 46, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS leads to cell death via protein, lipid, and DNA damage 45, 46, 48 . There is also evidence that sub-chronic exposure to adult zebrafish causes neurological effects associated with spatial recognition memory and behavior 52 . Several studies implicate TiO 2 nanoparticle coating, shape, size, and aggregation properties as confounding variables to these nanoparticle’s bioavailability and toxicity 45, 46, 50, 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al [81] also evaluated TiO 2 nanoparticle-induced neurotoxicity using zebrafish model. It has been reported that TiO 2 nanoparticle significantly activated expressions of different genes such as BDNF C-fos and C-jun.…”
Section: Different Assessment Methods To Evaluate Nanoparticle Toxicitymentioning
confidence: 99%
“…The zebrafish is a vertebrate model that has been used extensively to evaluate NP toxicity (Harper et al 2015;Wehmas et al 2015;Sheng et al 2016;Ginzburg et al 2018;Nix et al 2018). It was recently reported that exposure of embryonic zebrafish to Ag-NPs at concentrations far greater than those observed in the environment caused morphological and physiological abnormalities (Cunningham et al 2013;Gao et al 2015).…”
Section: Introductionmentioning
confidence: 99%